El Podcast y las competencias comunicacionales en segundo año de Bachillerato "B" de la UEP "José Antonio Eguiguren-La Salle", Loja 2023 - Guamán Pineda, Michael Janner (2023)
Podcasting is a normalized fact nowadays, allowing the student to develop without fear and thus strengthening their communication skills. In order to deepen this relationship, a general objective is proposed: To analyze the incidence of the podcast through a pedagogical proposal for the improvement of communicational competencies in second year of Bachillerato "B" of the UEP "José Antonio Eguiguren-La Salle", Loja 2023 and, three specific objectives a) To diagnose the communicational competencies that the students have acquired in their educational process; b) To elaborate a pedagogical proposal based on the podcast for the improvement of the students' communication skills; c) To evaluate the pedagogical proposal based on the podcast for the improvement of the students' communication skills. The sample consisted of 21 students and 1 teacher from an educational center in Lojano. A descriptive analysis was carried out and surveys, interviews, tables and graphs were used. The results show that 64% of the students are afraid of speaking in public, on the other hand, 100% of the teachers do not know the concept or methodology to improve the communication skills of their students. The sample consisted of 21 students and 1 teacher from an educational center in Lojano. A descriptive analysis was carried out and surveys, interviews, tables and graphs were used. The results show that 64% of the students are afraid of speaking in public, on the other hand, 100% of the teachers do not know the concept or methodology to improve communication skills in their students. We conclude by highlighting the relationship of the podcast and how it can influence the proper development of communication skills and alert to the urgent need to apply a strategy that involves the improvement of these capabilities in students to improve their communication skills. Keywords: Podcast, competencias skills, competencias communication, language-skills.